The Dynamics Of The Role Of Legal Politics In The Formation Of Regional Regulations (A Review Of Regional Regulation Of DKI Jakarta Number 2 Of 2020 Regarding The Handling Of Covid-19) - Gilang Abi Zaifa (Universitas Sains dan Teknologi Komputer, 2024)
As a legal state, Indonesia's foundation for law formation is intricately connected with legal politics. Legal politics play a crucial role in shaping legislative regulations in Indonesia. Legislative regulations serve as the primary method for creating laws and form an essential element within the national legal system of Indonesia. The research method employed is qualitative research, specifically a literature review. The findings of this research underscore the necessity for guidelines in the process of legislating to create laws that safeguard the population, ensure fair treatment, and protect citizens' rights. Consequently, the legal politics of legislative regulation formation represent a political policy aimed at establishing universally applicable legal rules with the objective of strengthening the sustained development of legislative regulations. These legislative regulations can also take the form of regional regulations, which, too, originate from a process of legal politics.